2016
DOI: 10.1242/jcs.181230
|View full text |Cite
|
Sign up to set email alerts
|

Pellicle formation in the malaria parasite

Abstract: The intraerythrocytic developmental cycle of Plasmodium falciparum is completed with the release of up to 32 invasive daughter cells, the merozoites, into the blood stream. Before release, the final step of merozoite development is the assembly of the cortical pellicle, a multi-layered membrane structure. This unique apicomplexan feature includes the inner membrane complex (IMC) and the parasite's plasma membrane. A dynamic ring structure, referred to as the basal complex, is part of the IMC and helps to divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 35 publications
(51 reference statements)
2
41
0
Order By: Relevance
“…Very few basal localised proteins have been described in invasive stages in Plasmodium . Recently a transmembrane protein localising at the basal rim of nascent IMC was reported in blood stage parasites 6 . While many apically localised protein have been reported both in Toxoplasma and Plasmodium , very few have been characterised during ookinete or sporozoite stages 5 8 , 12 , 24 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few basal localised proteins have been described in invasive stages in Plasmodium . Recently a transmembrane protein localising at the basal rim of nascent IMC was reported in blood stage parasites 6 . While many apically localised protein have been reported both in Toxoplasma and Plasmodium , very few have been characterised during ookinete or sporozoite stages 5 8 , 12 , 24 26 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that a pellicle protein, BTP1 is localised to the basal rim of the IMC during P . falciparum schizogony and co-localises with MORN1 6 . The presence of MORN1 in our interactome data suggests that PhIL1 may also be part of the basal complex in P .…”
Section: Discussionmentioning
confidence: 99%
“…This was key to understanding the mechanism of action of imidazopyrazines, a new antimalarial compound class that influence PPM development by blocking a lipid kinase involved in this process 15 . Furthermore, GFP-tagging of the PPM-localized putative sphingomyelin-synthethase (PfSMS1) allowed studying the interaction of the PPM with the inner membrane complex during blood stage development 16 . However, a similar PPM reporter parasite line for the mosquito and liver stages of the parasite has not so far been established.…”
Section: Introductionmentioning
confidence: 99%
“…The basal complex marker BTP1 has recently been shown to mark the basal rim of the forming IMC which can be seen as a contractile ring that advances in synchrony with plasma membrane invagination during cell division (Kono et al, ). Observation of the control parasites transfected with a BTP1‐GFP construct showed a labelled basal complex in segmented schizonts (Figure c(i)).…”
Section: Resultsmentioning
confidence: 99%